2019
DOI: 10.1016/j.ejso.2018.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Conversion due to vascular injury during video-assisted thoracic surgery lobectomy: A multicentre retrospective analysis from the Italian video-assisted thoracic surgery group registry

Abstract: Objectives: Vascular injuries are among the most severe causes of unplanned conversion during VATS lobectomies. The study aimed to analyse the incidence of vascular injuries and their risk factors during VATS lobectomy. Methods: The Italian VATS lobectomy Registry was used to collect data from 66 Thoracic Surgery Units. From 2013 to October 2016 (out of more than 3,700 patients enrolled) only information from Units with an enrollment >100 VATS lobectomies were retrospectively analysed. Logistic regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Respiratory complications were more common in the conversion group (p = 0.012), but accidental thoracotomy did not increase the overall surgical morbidity and mortality [40]. A multi-center retrospective analysis in Italy showed that unplanned thoracotomy was signi cantly associated with postoperative morbidity [15]. Among Bertolaccini L's research, intraoperative vascular injury, pleural adhesions, age > 60 years and resection locations were all factors that affect the incidence of PCCs and mortality.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Respiratory complications were more common in the conversion group (p = 0.012), but accidental thoracotomy did not increase the overall surgical morbidity and mortality [40]. A multi-center retrospective analysis in Italy showed that unplanned thoracotomy was signi cantly associated with postoperative morbidity [15]. Among Bertolaccini L's research, intraoperative vascular injury, pleural adhesions, age > 60 years and resection locations were all factors that affect the incidence of PCCs and mortality.…”
Section: Discussionmentioning
confidence: 98%
“…Among Bertolaccini L's research, intraoperative vascular injury, pleural adhesions, age > 60 years and resection locations were all factors that affect the incidence of PCCs and mortality. Experience was an independent factor to predict conversion [15]. However, studies of the same type put forward different points of view.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…invasive pulmonary resection (4). Once the main vessel is injured during operation, conversion to thoracotomy is an unavoidable consequence in some scenarios (8,10,15,16).…”
Section: A B C Dmentioning
confidence: 99%
“…Among these cases, 88 (3%) patients suffered from intraoperative bleeding due to vascular injury, and 70 (79.5%) cases were converted to open surgery (34). A recent study of the Italian VATS lobectomy registry enrolled 1,679 cases from ten high-volume centers found that the bleeding-related conversion rate was 2.6% among all the patients (37). Massive bleeding from vascular injury prolongs hospital stay and increases hospitalization costs significantly (30).…”
mentioning
confidence: 99%